(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Digitalization is radically transforming the banking industry, enabling new products, services and business models. This transformation will take time to complete, forcing banks to act now and embrace new technologies for a sustainable business strategy.As more and more people engage with the new technologies, it is changing nearly every business model. Customer on boarding and engagement, underwriting and risk management, billing and claims - all these areas are being changed by the digital innovations. The new wave comes with the power of innovation the digital transformation of the banking is one of the key challenges ahead - and certainly a big opportunity for the industries to renew themselves. Customer satisfaction is a critical issue in the success of any business system, traditional or online. In a turbulent commercial environment, in order to sustain the growth and market share, companies need to understand how to satisfy customers, since customer satisfaction is critical for establishing long term client relationships. It is evidenced by the fact that over the last five years, customer satisfaction surveys have become common in many financial institutions. Thus a fundamental understanding of factors impacting customer satisfaction is of great importance to business. This paper focus on challenges being faced by the bank in increasing customer satisfaction in the marketing of digital banking products.